Kecerdasan Emosional dan Hardiness Pada Ibu Rumah Tangga Single Parent - Ahmad Ahmad (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2015)
This study examined the relationship between emotional intelligence and personality competence. The subjects were mothers of single parent as much as 70 by using of accidental sampling. Data retrieval is done using a scale of emotional intelligence and hardiness scale. The data was then processed using the statistical parametric Pearson product moment The analysis shows that there is a relationship between emotional intelligence and hardiness in mother single parent. This shows that higher emotional intelligence, the higher the hardiness in mother single parent Key words: emotional intelligence, hardiness, single parent mother